A Strategic Partnership EU-AU. A joint vision for a common security - Luís Manuel Brás Bernardino (Cadernos de Estudos Africanos)
In a global context of high complexity, the relationship between Europe and Africa has recently faced some security challenges. Although the EU-Africa or EU-AU summits seek to contribute to strengthening strategic cooperation between organisations, it has not been very successful. This article, based on a documentary analysis and the need to respond to the challenges of the future points to a need to have a joint vision of security problems and seek joint, integrated, and strategic solutions. The biggest challenge for the future of the EU-AU relationship will be to build a genuine strategic partnership and collaborate on a joint vision that contributes to improving the capacity for a joint response to emerging security problems affecting the Euro-African area.